Preparation of hydrogel with processed honey / Muhamad Afiq Haziq Suharzeli - Suharzeli, Muhamad Afiq Haziq (2023)
Preparation of hydrogel wound dressing from processed honey are one of the purposes to further improve the use of honey in wound care and for convenience. A hydrogel that contains honey that has been processed by stingless bees and could be utilised as a material for treating wounds is created using layers of chitosan /PVA. The aim of this research is to do the research of the prepared hydrogel's tensile strength, porosity, and gel fraction and to prepare the hydrogel wound dressing with containing process honey at selected temperature. First things first, the preparation of process honey has been done to remove the crystallization and reduce the ability to fermentation that can cause deterioration. After the samples of treated honey being tested to make the best choice which temperature is better for hydrogel wound dressing. pH, Refractive Index, moisture content and hygroscopicity has been tested to determine which temperature is the best. From that, sample 60°C treated honey has been choose to be the best temperature for treated honey. Last but not least, the preparation of hydrogel from the best sample. The optimal temperature is determined by dividing the honey into three batches and heating them at varying temperatures during the manufacturing process.